TINGKAT KESEGARAN JASMANI PESERTA SENAM LANSIA PASIEN PROLANIS DI POLIKLINIK TELAGA MEDIKA GUBUG KABUPATEN GROBOGAN TAHUN 2014 (Department of Sports Science, Faculty of Sports Science, Universitas Negeri Semarang, 2014)
Tujuan penelitian ini adalah mengetahui tingkat kesegaran jasmani peserta senam lansia pada pasien PROLANIS di Poliklinik Telaga Medika Gubug Kab. Grobogan. Metode yang digunakan dalam penelitian kuantitatif ini adalah metode survei hasil tes kesegaran jasmani. Populasi pada penelitian ini adalah 97 lansia pada peserta senam lansia pasien PROLANIS Polikinik Telaga Medika Gubug Kab. Grobogan. Sampel penelitian ini sebanyak 30 lansia dengan teknik pengambilan sampel menggunakan teknik Purposive Sampling. Variabel penelitian ini terdiri dari tes tingkat kesegaran jasmani. Instrumen tes komposisi tubuh menggunakanÂ pengukuran Indeks Massa Tubuh (IMT) dan persen lemak tubuh (% lemak tubuh), Tes kapasitas kardiopulmonal (VO2maks), tes fleksibilitas, tes kekuatan otot tungkai, tes kekuatan otot togok, dan tes kekuatan otot genggaman tangan. Teknik analisis data berupa statistik deskriptif prosentase atau distribusi frekuensi relatif. Hasil penelitian tes kesegaran jasmani komposisi tubuh denagan pengukuran IMT 53,3% kategori obesitas, 46,7% dalam kategori normal dan pengukuran % lemak tubuh 53,3% kategori obesitas, 26,7% kategori kegemukan, 10% dalam kategori gemuk, dan (10%) dalam kategori normal. Tes VO2maks 46,7% kategori cukup, 40% kategori kurang, dan 13,3% kategori kurang sekali. Tes fleksibilitas 10% kategori baik, 60% kategori sedang, dan 30% kategori kurang. Tes kekuatan otot tungkai40% kategori baik, 60% kategori sedang. Tes kekuatan otot togok40% kategori baik, 60% kategori sedang. Tes kekuatan otot genggaman tangan 33,3% kategori sedang, 50% kategori kurang, 16,7% kategori kurang sekali. Simpulan penelitian ini secara umum kesegaran jasmani peserta senam lansia pasien PROLANIS di Poliklinik Telaga Medika Gubug Kab. Grobogan masuk dalam kategori sedang. Saran yang diberikan pada penelitian ini untuk menambah aktivitas fisik atau penambahan frekuensi olahraga lansia. Olahraga yang cocok untuk lansia antara lain jalan kaki, bersepeda, dan berenangThe purpose of this research is to know the level of physical fitness gymnastics participants PROLANIS in elderly patients of clinic Telaga Medika Gubug Kab. Grobogan. The methods used in the study of quantitative survey method is where the research data describes a number of physical fitness test results. The population in this research is 97 elderly patients elderly gymnastics participants in PROLANIS Polikinik Telaga Medika Gubug Kab. Grobogan. The sample of this research as many as 30 elderly with sampling techniques using a Purposive Sampling technique. This research consists of a variable-level test of physical fitness. Body composition test instrument use body mass Index measurements (IMT) and percent body fat (% body fat), vital lung capacity Tests (VO2Max), tests the flexibility, tests the strength of leg muscles, test the strength of back muscles, and tests the strength hands grip. Technique of data analysis in this study is a descriptive statistics percentage or relative frequency distribution. Results of research of physical freshness test, body composition measurement of IMT assembled 16 elderly or obese categories, 53,3% 14 elderly or 46,7% in the category of normal and 16% body fat measurement elderly or obese categories, 53,3% 8 elderly or 26.7% category 3 overweight elderly or 10% in the category of obese elderly person, and 3 or 10% in the normal category. VO2Max test 14 elderly or 46,7% category quite elderly, 12 or 40% less, and category 4 elderly or 13.3% less category once. 3 flexibility test for elderly or 10% good categories, 18 elderly or 60% category are elderly, and 9 or 30% less categories. Test the strength of limb muscles 12 elderly or 40% good, 18 elderly category or category was 60%. Tests of muscle strength togok 12 elderly or 40% good, 18 elderly category or category was 60%. Hand grip muscle strength test of 10 elderly or 33.3% category are elderly, 15 or 50% less category, 5 elderly or 16.7% less category once. A summary of the research of physical fitness in general elderly patients PROLANIS gymnastics participants in Telaga Medika Clinic Gubug Kab. Grobogan belongs to the category less. It can be seen from each test of physical fitness indicator to the elderly. The advice given in this study that the 30 elderly participants average gymnastics in a State or category less fresh it is referable to add physical activity or the frequency of addition of elderly sports regularly and in accordance with proficiency. A sport that is suitable for the elderly, among others, walking, cycling, and swimming, it is useful to keep the freshness of fitness as well as retaining his physical condition for prevention of various kinds of diseases